2019
DOI: 10.1016/s2542-5196(19)30237-2
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the variability in cardiovascular risk factors among First Nations communities in Canada: a population-based study

Abstract: Background Historical, colonial, and racist policies continue to influence the health of Indigenous people, and they continue to have higher rates of chronic diseases and reduced life expectancy compared with non-Indigenous people. We determined factors accounting for variations in cardiovascular risk factors among First Nations communities in Canada. MethodsMen and women (n=1302) aged 18 years or older from eight First Nations communities participated in a population-based study. Questionnaires, physical meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…Previous studies have investigated the association between social trust and proxy measures of MetS. In a Canadian paper that investigated the causes of health inequality, Indigenous people with higher social support were associated with a lower cardiovascular disease risk score [ 21 ]. Another study conducted with Americans aged 50 years and older, found a statistically significant association between higher perceived social cohesion and a lower incidence of stroke [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the association between social trust and proxy measures of MetS. In a Canadian paper that investigated the causes of health inequality, Indigenous people with higher social support were associated with a lower cardiovascular disease risk score [ 21 ]. Another study conducted with Americans aged 50 years and older, found a statistically significant association between higher perceived social cohesion and a lower incidence of stroke [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Recently, Anand and colleagues demonstrated that within FN communities across Canada, communities with greater trust among community members, higher socioeconomic status, higher social support, and higher education had lower rates of CVD risk factors. 39 Poorer medication literacy also positions Indigenous peoples at a disadvantage in receiving care; in an urban Indigenous health centre, Smylie and colleagues found that individuals with or at high risk of CVD had low CVD medication knowledge, placing them at risk for medication errors. 9 Encouragingly, implementation of an education program, which was delivered by a trained Indigenous nurse and included a tablet application, pill card, and booklet, was demonstrated to a significantly improve medication knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…20 More recent study involving Canadian First Nations communities (indigenous population) in 2018 showed that poor education, racism, di culty accessing routine health care and not having access to a primary health care provider are some of the risk factors associated with higher rates of cardiovascular disease. 19 Furthermore, it was revealed that greater the burden of socioeconomic hardship, the greater the burden of cardiovascular risk factors for a given community. 19 In a central Australian aboriginal community in 2009, depression and unemployment were identi ed as risk factors for having increased risk for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, it was revealed that greater the burden of socioeconomic hardship, the greater the burden of cardiovascular risk factors for a given community. 19 In a central Australian aboriginal community in 2009, depression and unemployment were identi ed as risk factors for having increased risk for cardiovascular disease. 20 In Sri Lanka, these scattered groups of indigenous populations are undergoing demographic transition (9.9% elders above 65 years in our study vs. 8.1% nationally).…”
Section: Discussionmentioning
confidence: 99%